Bioaccessibility and antioxidant activity of anthocyanins from jaboticaba skins: the influence of OSA-modified starch concentration - Michele Amendoeira Giaconia; Marcelo Assis; Milena da Silva Moura; Matheus Boeira Braga; Anna Rafaela Cavalcante Braga (Food Materials Research, 2023)
In recent years, there has been a growing interest in clarifying the metabolism of bioactive compounds, particularly phenolics such as anthocyanins. The transformation of anthocyanins from jaboticaba throughout digestion has yet to be extensively investigated. Due to native-form anthocyanins' instability against environmental stress, bioactive compounds are not always as effective in improving human health as they could be. The microencapsulation of material with high levels of anthocyanins by freeze-drying usually results in products with greater stability during storage, preserving their antioxidant properties. Therefore, the main goal of the present study was to determine the bioaccessibility of anthocyanins in jaboticaba powder samples to evaluate the effects of the modified starch with octenyl succinic anhydride (OSA) concentration (10% of adjuvant (PA), jaboticaba powder with 15% of adjuvant (PB), jaboticaba powder with 20% of adjuvant (PC), jaboticaba powder with 25% of adjuvant (PD)) using a static in vitro model of digestion over the anthocyanin’s contents and their antioxidant activities. Based on the results, it is possible to observe a decrease in anthocyanin content after the simulated digestive process. Before the digestion, the anthocyanins concentration values ranged from 94.30e ± 4.1 to 257.95a ± 22.8 ug/mL of cyanidin 3-glucoside. The highest concentration was found on jabuticaba pulp (JP) and the lowest on jaboticaba powder with 25% OSA-modified starch (PD). However, after the in vitro digestion, the loss of anthocyanins was more accentuated in the samples JP, PC, and PD. The bioaccessible anthocyanins varied from 5.30 (PC) to 9.58 (PB). Therefore, the PB sample presented the best results among the studied in the present work. The interaction between adjuvant and bioactive compounds promoted the protection of bioactive compounds against adverse digestion conditions, considering the maintenance of antioxidant activity.